Contribuição do polimorfismo rs686 no gene DRD1 para a dificuldade de aprendizagem da matemática em uma amostra populacional de crianças em idade escolar - Carolina de Castro Andrade Jorge (2022)
Math Learning Disabilities (MLD) is a cognitive development disorder that affects an individual's ability to acquire numerical and arithmetic skills. The frequency of MLD ranges from 1 to 8% among school-age children. MLD is a multifactorial characteristic and can be caused by social, emotional, economic, neurodevelopmental and genetic variables. MLD can negatively influence the individual's family, professional, social, emotional and intellectual context. Our research group investigated the contribution of dopaminergic system genes (DAT1 and COMT) to working memory and AMD in school-age children. The D1 dopamine receptor (encoded by the DRD1 gene) is the main target of dopamine in the prefrontal cortex. The expression of the DRD1 gene is in part modulated by the rs686 polymorphism, which has two alleles, G and A. The G allele in the 3'-UTR affects miR-504 binding and is associated with a decrease in D1 receptor expression. This study aimed to analyze the contribution of the D1 dopaminergic receptor to AMD and related phenotypes, using the functional polymorphism rs686 as a marker. A total of 574 children (254 boys) enrolled in the 2nd to 4th grades of Elementary School in Belo Horizonte (MG) or Porto Alegre (RS) were genotyped. School performance tests (Arithmetic TDE and spelling TDE), intelligence (Raven Progressive Color Matrices), working memory (Corsi Cubes and Digit Span - forward and backward), among others, were performed. Genotyping of rs686 was performed by High Resolution Melting (HRM). The effect of rs686 was evaluated under codominant, A-dominant, G-dominant and heterosis genotypic models using Mann Whitney U test and Kruskal-Wallis ANOVA, using SPSS v.25. There was a significant association between the genotype, under the G-dominant model, with the results of forward Corsi Cubes in both sexes, tested separately. Interestingly, the effect of genotypes was inverted according to sex. In multivariate ANOVA models considering both sexes together, an effect of the sex genotype interaction on the results of the forward Corsi Cubes task is observed. As expected, the magnitude of the genotype effect is small (adjusted r2=0.16). In boys, the A/G + G/G genotypes were associated with worse performance than the A/A genotype (median test, p=0.022; Mann-Whitney U, p=0.017). In girls, the A/G + G/G genotypes were associated with better performance when compared to the A/A genotype (median test, p=0.017; Mann-Whitney U, p=0.012). Models based on multivariate ANOVA, investigating the effects of sex, genotype, and results in the forward Corsi Cubes task on performance in the arithmetic TDE were not significant. Gender effects on visuospatial TM tasks have been described previously, but the effect of sex and genotypic model in general has not been investigated. This is the first study to investigate the effects of gender, rs686 under different models and their interaction on outcomes on a working memory task and performance in arithmetic.